Case Report: Successful Cerebral Revascularization and Cardiac Transplant in a 16-Year-Old Male With Syndromic BRCC3-Related Moyamoya Angiopathy - Pyra, Pierrick; Darcourt, Jean; Aubert-Mucca, Marion; Brandicourt, Pierre; Patat, Olivier; Cheuret, Emmanuel; Brochard, Karine; Sevely, Annick; Calviere, Lionel; Karsenty, Clément (Frontiers in Neurology, 2021)
Background:BRCC3/MTCP1 deletions are associated with a rare familial moyamoya angiopathy with extracranial manifestations. Case: We report the case of an adolescent male presenting with progressive and symptomatic moyamoya angiopathy and severe dilated cardiomyopathy caused by a hemizygous deletion of BRCC3/MTCP1. He was treated for renovascular hypertension by left kidney homograft and right nephrectomy in infancy and had other syndromic features, including cryptorchidism, growth hormone deficiency, and facial dysmorphism. Due to worsening of the neurological and cardiac condition, he was treated by a direct superficial temporal artery to middle cerebral artery bypass to enable successful cardiac transplant without cerebral damage. Conclusions:BRCC3-related moyamoya is a devastating disease with severe heart and brain complications. This case shows that aggressive management with cerebral revascularization to allow cardiac transplant is feasible and efficient despite end-stage heart failure.